Novel Development of Pasta Enriched with Spirulina platensis Microalgae: Biochemical and Histological Parameters - El-Sharnouby, Gamal; Abughoush, Mahmoud; Choudhury, Imranul (Jordan Journal of Agricultural Sciences, 2024)
The present study aims to determine the effect of bioactive compounds (total phenolic, total flavonoids, and antioxidant activity) of Spirulina platensis powder and its pasta products on kidney and liver diseases in rats. Pasta preparation enriched in spirulina powder with a standard treatment formulation. Pasta was supplemented by adding Spirulina platensis powder at different levels (5, 10, 15, and 20 %). The results indicated that rats treated with spirulina had lower plasma levels of ALT, AST, ALP, Albumin, creatinine, and total bilirubin after the end of the experiments. However, liver glutathione (GSH) concentration was markedly decreased as compared to the control group. In conclusion, pasta enriched with spirulina improved liver and kidney functions and enhanced oxidative stress indices. Additional studies are necessary to test the application of Spirulina platensis in other contexts.